Progress in environmental-friendly polymer nanocomposite material from PLA: synthesis, processing and applications - Dubey, Satya P.; Thakur, Vijay Kumar; Krishnaswamy, Suryanarayanan; Abhyankar, Hrushikesh; Marchante, Veronica; Brighton, James L. (Elsevier, 2017)
The disposal of large amounts of waste from daily use polymers is among one of the foremost concerns in the current era. Effective utilization of bio-renewable materials procured from natural sources has been proposed as a potential solution to this problem. Among such different polymers, Poly lactic acid (PLA) which is a bio-degradable polymer, resembles quite promotable features, which can be polymerized from sustainable sources as chips sugarcane, starch and corn. Ring-opening polymerization (ROP) of Lactide (LA) monomer considering catalysts such as Al, Sn or Zn is one of the efficient methods for the PLA synthesis. However, the PLA polymerized through this type of catalysts may contain trace elements of the catalyst. Due to their carcinogenic nature, the traces of such catalysts should be (ideally) removed from the synthesis process. The use of alternative energy (AE- UV, Microwave) sources could be a potential route. Alternative development of non-metal catalysts is best alternatives for the processing of PLA through ROP. PLA layer based composite materials are gaining huge interest due to their multiple application (food, medical etc.) as eco-friendly material. In this article, we review on the implementation of AE sources for PLA processing and to populate the current state-of-the-art associated with the PLA research, especially application in nanocomposite materials field.
Keywords: Poly-lactic acid (PLA); Bio-degradable materials; Ring opening polymerization (ROP); Nano-composite; Alternative energy (AE)